Contraceptive use and method preference among women in Soweto, South Africa: the influence of expanding access to HIV care and treatment services. - Angela Kaida (PLoS ONE, 2010)
Preventing unintended pregnancy among HIV-positive women constitutes a critical and cost-effective approach to primary prevention of mother-to-child transmission of HIV and is a global public health priority for addressing the desperate state of maternal and child health in HIV hyper-endemic settings. We sought to investigate whether the prevalence of contraceptive use and method preferences varied by HIV status and receipt of highly active antiretroviral therapy (HAART) among women in Soweto, South Africa.We used survey data from 563 sexually active, non-pregnant women (18-44 years) recruited from the Perinatal HIV Research Unit in Soweto (May-December, 2007); 171 women were HIV-positive and receiving HAART (median duration of use = 31 months; IQR = 28, 33), 178 were HIV-positive and HAART-naïve, and 214 were HIV-negative. Medical record review was conducted to confirm HIV status and clinical variables. Logistic regression models estimated adjusted associations between HIV status, receipt of HAART, and contraceptive use.Overall, 78% of women reported using contraception, with significant variation by HIV status: 86% of HAART users, 82% of HAART-naïve women, and 69% of HIV-negative women (p<0.0001). In adjusted models, compared with HIV-negative women, women receiving HAART were significantly more likely to use contraception while HAART-naïve women were non-significantly more likely (AOR: 2.40; 95% CI: 1.25, 4.62 and AOR: 1.59; 95% CI: 0.88, 2.85; respectively). Among HIV-positive women, HAART users were non-significantly more likely to use contraception compared with HAART-naïve women (AOR: 1.55; 95% CI: 0.84, 2.88). Similar patterns held for specific use of barrier (primarily male condoms), permanent, and dual protection contraceptive methods.Among HIV-positive women receiving HAART, the observed higher prevalence of contraceptive use overall and condoms in particular promises to yield fewer unintended pregnancies and reduced risks of vertical and sexual HIV transmission. These findings highlight the potential of integrated HIV and reproductive health services to positively impact maternal, partner, and child health.